МАКТАБ РАҲБАРЛАРИНИНГ БОШҚАРУВ САЛОҲИЯТИНИ СЕЛФ-МЕНЕЖМЕНТ АСОСИДА РИВОЖЛАНТИРИШНИНГ ПЕДАГОГИК ИМКОНИЯТЛАРИ - Кудиярова, Г.И. (SCIENCE and SOCIETY, 2025)
The article analyzes the scientific-theoretical and practical aspects of developing the managerial potential of general education school leaders based on self-management. It substantiates the necessity of personal and professional development of school leaders in the context of globalization and digital transformation, the formation of strategic thinking, the implementation of innovative ideas, as well as the effective application of reflection and self-assessment mechanisms.